Agricultural adaptations to topography and climate changes in Central China during the mid- to late-Holocene. (December 2021) - Jia, Xin; Li, Haiming; Lee, Harry F; Liu, Zhen; Lu, Yong; Hu, Zhujun; Sun, Xueqiang; Zhao, Zhijun
The development of pre-historic agriculture and its determining factors have been extensively investigated in recent years. Based on the identification of charred seeds and radiocarbon dating, we found that foxtail millet-based agriculture dominated Neixiang County in Central China during the mid-late-Holocene. There were three different farming patterns in the Nanyang Basin, including rice cultivation in the plains, foxtail millet cultivation in the pediment plains, and broomcorn millet cultivation in the valleys. In addition, during the Neolithic-Bronze Age, the distribution of human settlements with rice cultivation matched with the climate pattern at 31.0–36.5° N in China. The emergence of rice cultivation had been facilitated by a significant increase in East Asian summer monsoon and increased precipitation in Central China since 8500 BP and gradually flourished during the Peiligang (8500–7000 BP) and Yangshao (7000–4500 BP) Period, corresponding to a relatively warm and wet climate. However, the average latitude of the human settlements with rice cultivation shifted southward to 33.29° N during the Longshan Period (4500–4000 BP) due to the cold climate brought by the "4.2 ka event." Afterward, rice cultivation was basically not constrained by climate change, probably owing to the improved farming methods in the Bronze Age.